2020
DOI: 10.1051/0004-6361/201936843
|View full text |Cite
|
Sign up to set email alerts
|

The binary content of multiple populations in NGC 3201

Abstract: We investigate the binary content of the two stellar populations that coexist in the globular cluster NGC 3201. Previous studies of binary stars in globular clusters have reported higher binary fractions in their first populations (P1, having field-like abundances) compared to their second populations (P2, having anomalous abundances). This is interpreted as evidence for the latter forming more centrally concentrated. In contrast to previous studies, our analysis focuses on the cluster centre, where comparable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…To give a few examples, Deacon and Kraus [20] found a measurable difference in the wide-binary frequency between open clusters and moving groups. In the globular cluster NGC 3201, Kamann et al [21] measured a binary frequency of 23.1 ± 6.1% in the first population of stars and 8.2 ± 3.5% in the second-generation population that formed later in a more dynamically active environment.…”
Section: Statistical Trendsmentioning
confidence: 99%
“…To give a few examples, Deacon and Kraus [20] found a measurable difference in the wide-binary frequency between open clusters and moving groups. In the globular cluster NGC 3201, Kamann et al [21] measured a binary frequency of 23.1 ± 6.1% in the first population of stars and 8.2 ± 3.5% in the second-generation population that formed later in a more dynamically active environment.…”
Section: Statistical Trendsmentioning
confidence: 99%
“…If at all, we see some stars with an excess metallicity. The binary content of multiple populations in NGC 3201 is investigated in detail in Kamann et al (2020).…”
Section: Ngc 3201mentioning
confidence: 99%
“…On the other hand a range of Fe is not found by Cabrera-Ziri et al ( 2019) along the extended P1 sequence of NGC 2808. A recent analysis by Martins et al (2020) has also excluded binaries (see also Kamann et al 2020) and chromospheric activity as explanations for the observed extended P1 sequences.…”
Section: Pseudocolours and Chromosome Mapsmentioning
confidence: 99%